Peculiarities of the exciton scattering in double semiconductor quantum wells with disordered layers - Vertsimakha, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Effects of the presence of isolated disordered layers on the exciton scattering by compositional fluctuations in double semiconductor quantum wells have been studied. In the structures containing both ordered and disordered layers, the probability of the scattering depends on the degree of the exciton wavefunction localization in the disordered layers, where it interacts with the fluctuations. For some parameters of the structure the exciton wavefunction can penetrate deeply into the ordered layers of the structure, which leads to a sharp drop of the probability of the scattering and, consequently, to the narrowing of the optical exciton bands. It has been shown that for heterostructures containing diluted magnetic semiconductor layers, the probability of the scattering can be tuned by external magnetic field.